2019
DOI: 10.1136/jmedgenet-2019-106221
|View full text |Cite
|
Sign up to set email alerts
|

Genetic aetiology of early infant deaths in a neonatal intensive care unit

Abstract: BackgroundCongenital anomalies are the leading cause of early neonatal death in neonatal intensive care units (NICUs), but the genetic causes are unclear. This study aims to investigate the genetic causes of infant deaths in a NICU in China.MethodsNewborns who died in the hospital or died within 1 week of discharge were enrolled from Children’s Hospital of Fudan University between January 1, 2015 and December 31, 2017. Whole exome sequencing was performed in all patients after death.ResultsThere were 223 decea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 44 publications
0
34
1
Order By: Relevance
“…Little, however, has yet been published with regard to the contribution of genetic diseases to infant mortality using this technology. In six published studies and the cohort reported herein a weighted average of 21% of infant deaths was attributable to single locus genetic diseases 25 , 28 , 45 , 63 65 . However, the range of attribution varied widely between studies (6%-86%), reflecting different experimental designs and inclusion and exclusion criteria.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Little, however, has yet been published with regard to the contribution of genetic diseases to infant mortality using this technology. In six published studies and the cohort reported herein a weighted average of 21% of infant deaths was attributable to single locus genetic diseases 25 , 28 , 45 , 63 65 . However, the range of attribution varied widely between studies (6%-86%), reflecting different experimental designs and inclusion and exclusion criteria.…”
Section: Discussionmentioning
confidence: 92%
“…To evaluate whether the findings reported herein were generalizable, we searched the literature for genomic sequencing studies in acutely ill infants in which mortality was recorded. Six additional studies were identified that utilized current genetic disease databases and current variant detection and interpretation methods (Table 4 ) 25 , 28 , 45 , 63 – 66 . Three studies had similar experimental designs as herein–diagnostic genomic sequencing was performed in infant inpatients in United States hospitals who had acute diseases of unknown etiology and in whom genetic diseases were suspected 25 , 28 , 45 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations